Fatigue Resistant Aerogel/Hydrogel Nanostructured Hybrid for Highly Sensitive and Ultrabroad Pressure Sensing. Issue 1 (6th December 2021) - Huang, Jiankun; Zeng, Jingbin; Zhang, Xue; Guo, Gengchen; Liu, Rui; Yan, Zifeng; Yin, Yadong
Abstract: Achieving high sensitivity over a broad pressure range remains a great challenge in designing piezoresistive pressure sensors due to the irreconcilable requirements in structural deformability against extremely high pressures and piezoresistive sensitivity to very low pressures. This work proposes a hybrid aerogel/hydrogel sensor by integrating a nanotube structured polypyrrole aerogel with a polyacrylamide (PAAm) hydrogel. The aerogel is composed of durable twined polypyrrole nanotubes fabricated through a sacrificial templating approach. Its electromechanical performance can be regulated by controlling the thickness of the tube shell. A thicker shell enhances the charge mobility between tube walls and thus expedites current responses, making it highly sensitive in detecting low pressure. Moreover, a nucleotide‐doped PAAm hydrogel with a reversible noncovalent interaction network is harnessed as the flexible substrate to assemble the aerogel/hydrogel hybrid sensor and overcome sensing saturation under extreme pressures. This highly stretchable and self‐healable hybrid polymer sensor exhibits linear response with high sensitivity ( S min > 1.1 kPa −1 ), ultrabroad sensing range (0.12–≈400 kPa), and stable sensing performance over 10 000 cycles at the pressure of 150 kPa, making it an ideal sensing device to monitor pressures from human physiological signals to significant stress exerted by vehicles. Abstract : Achieving high sensitivity of pressure over a broad range covering both subtle and extremely high pressure remains a challenge due to the unsatisfactory structural stretchability and compressibility of the sensing materials. This work addresses this issue by designing a hybrid structured aerogel/hydrogel sensor by integrating a nanotube structured polypyrrole aerogel with a polyacrylamide hydrogel.